Analysis Of Organizational Culture And Work Environment On Employee Performance At The Medan Perjuangan District Office - Aisyah Nurul Fasah Lbs; Sri Rahayu; M. Chaerul Rizky (Universitas Dehasen Bengkulu, 2026)
The research analysis aims to analyze the organizational culture and work environment on employee performance at the Medan Perjuangan District Office. The data analysis technique used is the associative research method with the help of the SPSS version 23 program. This study uses multiple linear regression analysis. The sample in this study was 100 respondents. Primary data collection used a questionnaire. The results of the study indicate that the organizational culture variable has a t count of 3.651 and a t table of 1.984723, so t count > t table (3.651 > 1.984723) with sig. 0.000 < 0.05 so that the results of the study accept H1. It can be explained that the organizational culture variable (X1) influences the employee performance variable of the Medan Perjuangan Sub-district Office. The work environment variable has a t count of 2.345 and a t table of 1.984723, so t count > t table (2.345 > 1.984723) with sig. 0.021 < 0.05 so that the results of the study accept H1. It can be explained that the work environment variable (X2) influences the employee performance of the Medan Perjuangan Sub-district Office. The value obtained is f count = 92.290 > f table 3.09 with sig. 0.000 < 0.05. So it can be concluded that H1 is accepted. Where the variables of organizational culture (X1) and work environment (X2) simultaneously have a positive and significant effect on the performance of employees at the Medan Perjuangan District Office.